Pengaruh Motivasi Dan Bimbingan Belajar Orang Tua Terhadap Prestasi Belajar Siswa Kelas Atas Di Sd Muhammadiyah 16 Karangasem Surakarta Tahun 2015/2016 - Adelina, Adelina, Minsih, S.Ag., M.Pd (2016)
This study aims to determine: (1) the effect of learning motivation on student achievement upscale, (2) the effect of tutoring parents on learning achievement upscale, and (3) the effect of learning motivation and tutoring parents on learning achievement upscale. This research uses quantitative research and research design Ex-Posfacto. The object of this study is upscale students (IV and V) which total number is 218 students of SD Muhammadiyah 16 Karangasem. A sample of 59 students by using proportionate stratified random sampling technique. The data analysis method is multiple regression. The results of this study indicate that: (1) there is learning motivation on learning achievement upscale in SD Muhammadiyah 16 Karangasem in 2015/2016 to obtain tcount 2,677> 2,002 ttable, and the effective contribution is 18,3458%. (2) there is tutoring parents on student achievement upscale SD Muhammadiyah 16 Karangasem in 2015/2016 to obtain tcount 2,758 > 2,002 ttable, and the effective contribution is 19,0784%. (3) there is motivation to learn and tutoring parents together on student achievement upscale SD Muhammadiyah 16 Karangasem in 2015/2016 to obtain the value of Fcount 16,744 > F table 3.15, the effective contribution of learning motivation and tutoring parents together on learning achievement is 37,4% and the remaining 62,6% is influenced by other factors. Based on the results of this study,it can be concluded that there are the effect significant of learning motivation and tutoring parents on learning achievement upscale in SD Muhammadiyah 16 Karangasem in 2015/2016.